A 3D fully Lagrangian Smoothed Particle Hydrodynamics model with both volume and surface discrete elements. (31st May 2013) - Amicarelli, Andrea; Agate, Giordano; Guandalini, Roberto
SUMMARY A 3D fully Lagrangian smoothed particle hydrodynamics (SPH) model has been developed adopting a particle approximation, which considers both volume and surface elements at boundaries. The model is based on the main principles of the 2D model of Ferrand et al. (2012) and on the spatial reconstruction schemes used in SPH–arbitrary Lagrangian–Eulerian modeling to treat boundaries (Marongiu et al., 2007). This model is conceived to represent free surface flows and their interactions with solid structures. It is validated on a 2D water jet impact over a plate, a sloshing tank test case, and two experimental 3D dam break fronts, which interact with fixed obstacles. The results are compared with the available measurements and analytical solutions. We finally provide supplementary inter‐comparisons using another SPH numerical model, based on the semi‐analytical approach.Copyright © 2013 John Wiley & Sons, Ltd.